2010
DOI: 10.1590/s1413-70542010000700001
|View full text |Cite
|
Sign up to set email alerts
|

Absorção, acúmulo e exportação de macronutrientes no milho doce cultivado em condições de campo

Abstract: RESUMOO milho doce é uma hortaliça voltada para o processamento industrial, é ainda pouco difundido para o consumo in natura no Brasil, talvez pelo restrito número de cultivares adaptadas ao clima tropical. Os estudos sobre as práticas de manejo mais adequadas, incluindo a dinâmica de absorção de nutrientes pela cultura, ainda são inexistentes. Portanto, neste trabalho, objetivou-se determinar a absorção, o acúmulo e a exportação de nutrientes no milho doce cultivado em condições de campo. Utilizou-se o híbrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 3 publications
0
2
0
6
Order By: Relevance
“…Still according to the previously mentioned authors, after N, K is the element absorbed in highest amount by corn and 30% is exported in the grains, which would explain the observed decrease. Evaluating the accumulation, extraction and dynamics of absorption of macronutrients by the corn crop, Borin et al (2010) observed higher K accumulation in the first 30 days of plant development and the increasing accumulation occurred until 45 days after sowing, followed by a decrease caused by the redistribution to the ear.…”
Section: Resultsmentioning
confidence: 97%
“…Still according to the previously mentioned authors, after N, K is the element absorbed in highest amount by corn and 30% is exported in the grains, which would explain the observed decrease. Evaluating the accumulation, extraction and dynamics of absorption of macronutrients by the corn crop, Borin et al (2010) observed higher K accumulation in the first 30 days of plant development and the increasing accumulation occurred until 45 days after sowing, followed by a decrease caused by the redistribution to the ear.…”
Section: Resultsmentioning
confidence: 97%
“…Pese a que el K es el nutriente más requerido por el maíz dulce (Maggio, 2006;Heckman, 2007;Borin, Lana y Pereira, 2010;Meneses, 2014), una gran cantidad de este elemento queda en la parte aérea, ya que solamente entre 12 % y 27 % son exportados por la mazorca. En este sentido, en razón de no ser constituyente estructural de moléculas y tejidos (Marschner, 1995;Cakmak, 2005;Mengel, 2007), el K puede estar fácilmente disponible durante el proceso de descomposición de los restos vegetales, teniendo implicaciones sobre la recomendación de este nutriente en los próximos ciclos de cultivo.…”
Section: Resultados Y Discusiónunclassified
“…A pesar de no formar parte de ninguna molécula orgánica o de la estructura de la planta, el K es el nutriente más acumulado por el maíz dulce (Maggio, 2006;Heckman, 2007;Borin, Lana y Pereira, 2010;Meneses, 2014), debido a que desempeña un papel fundamental en procesos como la fotosíntesis, osmorregulación, síntesis de proteínas, formación y translocación de carbohidratos y activación de enzimas (Mengel, 2007;Hawkesford et al, 2012), los cuales afectan directamente la productividad y calidad del maíz dulce (Cao et al, 2011).…”
Section: Introductionunclassified
“…Percebe-se que o maior acúmulo do potássio ocorreu dos 12 aos 22 DAE, Resultado semelhante foi encontrado por Borin et al (2010) e Primo et al (2012) estudando absorção, acúmulo e exportação de macronutrientes no milho doce cultivado em condições de campo verificou que o potássio apresentou alta taxa de acúmulo nos primeiros 30 dias de desenvolvimento, com ritmo de absorção superior ao N.…”
Section: Tratamentosunclassified